Improving heat recovery in retrofitting heat exchanger networks with heat transfer intensification, pressure drop constraint and fouling mitigation. (1st January 2016) - Pan, Ming; Bulatov, Igor; Smith, Robin
Highlights: New intensification techniques are implemented for HEN retrofitting. Fouling effects and pressure drop constraints are considered. A new modeling and optimization method is developed for the retrofit problems. The proposed methods can perform much better than the existing methods. The proposed methods are efficient for practical application. Abstract: Implementing heat transfer intensified techniques are now recognised as an efficient retrofit way of improving energy saving in heat exchanger networks (HENs). This not only increases heat recovery, but also prolongs exchanger operating time due to its effect on fouling mitigation. Compared with most of the existing work of HENs based on very simple assumptions for fouling effect, this paper addresses more accurate and complex fouling models reported recently (Yang et al., 2012). Due to the dynamic features of fouling, integration of dynamic equation of fouling rate is used to estimate fouling resistance at different operational times. The novelty of this paper is to present new insights to implementation of heat transfer intensified technologies for HEN retrofitting. It is the first study to implement hiTRAN ® (one commercial tube-insert technology) into heat exchangers to increase HEN heat recovery with the consideration of detailed exchanger performances including heat transfer intensifications, pressure drop constraints, and fouling mitigation. The overall retrofit profit is maximized based on the best trade-off among energy savings, intensification implementation costs, exchanger cleaning costs, and pump power costs. To solve such complex optimization problems, a new mixed-integer linear programming (MILP) model has been developed to consider fouling effects in retrofitting HENs with heat transfer intensification. An efficient iterative optimization approach is then developed to solve the MILP problem. In case studies, the new proposed approach is compared with the existing methods on an industrial scale problem, demonstrating that the new proposed approach is able to obtain more realistic solutions for practical industrial problems.